Rancang Bangun Prototype Sistem Informasi Pipe Reporting Berbasis Web pada SKK Migas - Rini Andriani; Samuel Anaya Putra Zai; Sindy Fitriani Margaret Sihaloho (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to develop an information system for 2 types of web-based Pipe Reporting, namely PVC Pipe Report and Steel Pipe Report which meets SKK Migas' needs in pipe data management. SKK Migas, as an institution managing oil and gas activities, requires an efficient and integrated solution for tracking, reporting and analyzing pipeline-related information. The proposed system is designed with a focus on ease of use, accessibility, and data reliability. The system development approach uses web-based technology to facilitate access from various locations. This research includes in-depth requirements analysis stages, measurable system architecture design, and prototype implementation. The success of the system is measured through increased efficiency in the pipeline data reporting, monitoring and analysis processes. It is hoped that the results of this research will not only meet SKK Migas' needs directly, but can also become a basis for developing similar systems in the oil and gas industry more broadly.